The Sustainability Status of Partnership of Palm Oil Plantations - Daud, Wilson; Panuntun, Sri (Universitas Muhammdaiyah Surakarta, 2015)
One of existence determining factor of PBS palm oil is a harmonious relation with communities surroundings, thus the partnership between the palm oil plantation with the farmers surroundings is one of effort which has created the harmonization in palm oil plantation. The objective of the article is to express the sustainability of each pattern of palm oil PBS partnership, and this partnership form gives the sustainability advantages for the farmer and palm oil PBS in Central Kalimantan. The article used quantitative method through the survey approach, primary data and secondary data. The article result there are three main patterns of palm oil plantation partnership in Central Kalimantan, they are MSA, KKPA, and IGA. IGA has value as a form which has degree of continuing that higher than MSA and KKPA, thus make IGA can be the reference in frame of PBS palm oil partnership in Central Kalimantan with keeping the superiority and improving the weaknesses.